1999
DOI: 10.1002/(sici)1097-0193(1999)7:1<49::aid-hbm5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized auditory spatial perception and the contralaterality of cortical processing as studied with functional magnetic resonance imaging and magnetoencephalography

Abstract: Functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) were used to study the relationships between lateralized auditory perception in humans and the contralaterality of processing in auditory cortex. Subjects listened to rapidly presented streams of short FM-sweep tone bursts to detect infrequent, slightly deviant tone bursts. The stimulus streams consisted of either monaural stimuli to one ear or the other or binaural stimuli with brief interaural onset delays. The onset delay gives th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
63
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(87 citation statements)
references
References 18 publications
21
63
3
Order By: Relevance
“…This ratio is similar to previously reported spatial tuning of auditory cortical neurons in mammals (Malhotra et al, 2004; Middlebrooks and Pettigrew, 1981; Rajan et al, 1990). Our findings, however, contrast with several neuroimaging studies in humans that report little to no contralateral bias (Woldorff et al, 1999; Zimmer et al, 2006). This discrepancy could be the result of bias-coding rather than place-coding of sound direction, which would not be easily detected in fMRI (Werner-Reiss and Groh, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…This ratio is similar to previously reported spatial tuning of auditory cortical neurons in mammals (Malhotra et al, 2004; Middlebrooks and Pettigrew, 1981; Rajan et al, 1990). Our findings, however, contrast with several neuroimaging studies in humans that report little to no contralateral bias (Woldorff et al, 1999; Zimmer et al, 2006). This discrepancy could be the result of bias-coding rather than place-coding of sound direction, which would not be easily detected in fMRI (Werner-Reiss and Groh, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that the contralateral auditory cortex was activated when unimodal auditory stimuli were presented in the left or right locations; this finding is consistent with previous studies [45]. However, no significant integration was found when visual stimuli were centrally presented and auditory stimuli were presented in the left (90°) or right (90°) location.…”
Section: Discussionsupporting
confidence: 93%
“…For comparison, we also applied this analysis to the left and right auditory cortex. Previous fMRI research has shown a contralateral bias in auditory cortex for monoaural stimulation [16][18]. But to date, fMRI research has not been able to detect a contralateral bias with binaural stimulation, even though subjects may report hearing the sound source to be lateralized to the left or right, e.g.…”
Section: Resultsmentioning
confidence: 96%